Microglial memory of early life stress and inflammation: Susceptibility to neurodegeneration in adulthood - Desplats, Paula (2019)
We review evidence supporting the role of early life programming in the susceptibility for adult neurodegenerative diseases while highlighting questions and proposing avenues for future research to advance our understanding of this fundamental process. The key elements of this phenomenon are chronic stress, neuroinflammation triggering microglial polarization, microglial memory and their connection to neurodegeneration. We review the mediating mechanisms which may function as early biomarkers of increased susceptibility for neurodegeneration. Can we devise novel early life modifying interventions to steer developmental trajectories to their optimum?.